PEMBUATAN BETON SELF COMPACTING CONCRETE (SCC) DENGAN VARIASI PASIR LOKAL UNTUK BETON PRECAST PADA BANGUNAN PELENGKAP JALAN - Indrayani . Indrayani (Jurnal Teknologi Terpadu, 2022)
Self Compacting Concrete (SCC) is a self-compacting concrete with a fairly high slump value. For the manufacture of Self Compacting Concrete (SCC) it will be faster and more economical so that it is able to produce precast concrete products that are planned for road complementary buildings. In this study, researchers used 3 variations of local sand from South Sumatra and added material in the form of superplasticizer ligno P-100 with levels of 1.5%, 2% and 2.5% by weight of cement. With the sample used in the form of a cube which is then tested for the physical properties of the fresh condition SCC concrete and testing the compressive strength of the concrete. From the test results, it was found that the variation of sand and the optimum superplasticizer content for the flow ability test on the coarse sand variation with the superplasticizer content of 2%, for passing ability, filling ability, and segregation resistance on the fine sand variation with the superplasticizer content of 2.5% with successive values. followed by 750 mm, 0.95, 0.94 and 11 seconds. So from all these tests have met the four requirements for the properties of SCC concrete.